A new species of the genus Aberrasine Volynkin & Huang from Xizang, China (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Zhu, Li-Juan; Volynkin, Anton V.; Singh, Navneet; Wang, Min; Fan, Xiao-Ling; Huang, Si-Yao (Zootaxa, 2021)
A new species of the genus Aberrasine Volynkin & S.-Y. Huang, 2019, Aberrasine tiani S.-Y. Huang, Volynkin, N. Singh & M. Wang, sp. nov. is described from southern Xizang, China. The species belongs to the A. strigivenata species-group having a characteristic reduced forewing pattern consisting of a medial transverse line and lengthwise strokes along veins. Adults and genitalia of the new and the similar species are illustrated.